Continuity and Discontinuity: Pentecostalism and Cultural Change in a Liberian Refugee Camp in Ghana - Ecke, Jonas Paul (PentecoStudies, 2015)
This article explores the cultural change generated by Pentecostalism among Liberian refugees in Ghana, who fled from their nation's civil wars to a refugee camp in Ghana's Central Region. Anthropologists of religion have argued that Pentecostal conversions have in large parts become popular because they enable a break with the past. Liberian converts, as well, seek to distance themselves from a past that is mired in conflict. To this end, they connect to global Pentecostal networks in an attempt to overcome their marginal status. In so doing, many of them reject aspects of their past, which they associate with the Liberian civil wars, for example traditional belief systems, ethnic identity, and the Liberian gerontocracy. Yet, as the ethnographic examples illustrate, this break with the past is rarely complete. This study's findings are related to debates on whether anthropology of religion should focus on continuity or discontinuity in exploring religious conversions. The author argues that the religious experiences of Liberians in exile can only be understood by paying attention to the interplay and tensions between continuity and discontinuity.